Investigating the Mediating Role of Mindfulness in Relation to Optimism and MentalVitality in Women with Autoimmune Disease - Karimian, Marzieh; Salehi, Seddiqa; Norouzi, Mona; Samavati, Mona; Rahimi, Leila (Shahroud Journal of Medical Sciences, 2024)
Background: The prevalence of certain autoimmune disorders among women is rising at a faster rate compared to men, potentially affecting the well-being of women globally. This study aimed to explore the moderating influence of mindfulness on optimism and mental energy among women diagnosed with autoimmune conditions.Methods: Descriptive-correlational and cross-sectional research methods, along with structural equation modeling (SEM), were utilized in this study. The research population consisted of all women with autoimmune diseases in Tehran from May to April 2023. A total of 204 women with autoimmune diseases were selected as the statistical sample using targeted sampling. The research utilized the Trauma Resilience Scale (TRS), Mental Vitality Questionnaire (MVQ), and Five Facet Mindfulness Questionnaire (FFMQ) as measurement tools. Descriptive statistics were analyzed using SPSS version 27 software, while path coefficients were analyzed using SmartPLS version 4 software. Additionally, Sobel's test was employed to determine the significance of the mediator variable. A significance level of 0.05 was considered. Results: Based on the findings optimism had a favorable and noteworthy influence on mental vitality (β=0.399, P<0.001). Similarly, the variable of optimism also had a favorable and noteworthy impact on accompanying action with awareness, description, no judgment, and view aspects (P<0.001). However, the optimism variable did not exhibit a significant influence on No reaction (P=0.134). Furthermore, a negative and significant correlation (β=-0.065, P=0.007) was identified between optimism and Mental vitality, with the intervening aspect of the no judgment component. Conversely, a positive and meaningful association (β=0.172, P<0.001) was observed between optimism, and mental vitality, with the involvement of the view component. Nonetheless, the indirect associations between optimism and mental vitality, with the mediating role of No reaction, accompanying action with awareness, and Description components, were not statistically significant (P>0.05). Conclusions: The results of the present study indicated that optimism increases mental vitality and the dimensions of mindfulness, of course, except for lack of reaction. And the mediating variable of mindfulness also has significant effects on optimism and mental vitality.